Theoretical production about Physical Exercise and Autistic Spectrum Disorder: a review study (Research, Society and Development, 2022)
Objective: to elucidate, through a review study, scientific evidence about physical exercise for people with autism spectrum disorder. Methods: this is a study of an integrative literature review, carried out in the BVS, Scielo and CAPES Periodical databases using the descriptors autistic spectrum disorder and physical exercise, as well as articles in English, Portuguese and Spanish, published between the years 2017 to 2022. Results: A total of 14 articles were identified that prove the importance and benefits of physical activity for people with autism spectrum disorder. Final Considerations: According to the studies addressed in the article, they aim to approach practices and adapt them to treat the stereotyped behaviors of people with Autism Spectrum Disorder. Related to regular physical activity, connected with other practices such as the personal connection with quadrupedal animals (cats, dogs, horses, among others), added with variations of exercises which include swimming, football, horseback riding and the relationship with the family nucleus, from the which include the friends of these individuals.